Food processing 4.0: Current and future developments spurred by the fourth industrial revolution. (March 2023) - Hassoun, Abdo; Jagtap, Sandeep; Trollman, Hana; Garcia-Garcia, Guillermo; Abdullah, Nour Alhaj; Goksen, Gulden; Bader, Farah; Ozogul, Fatih; Barba, Francisco J.; Cropotova, Janna; Munekata, Paulo E.S.; Lorenzo, José M.
Abstract: "Food processing 4.0" concept denotes processing food in the current digital era by harnessing fourth industrial revolution (called Industry 4.0) technologies to improve quality and safety of processed food products, reduce production costs and time, save energy and resources, as well as diminish food loss and waste. Industry 4.0 technologies have been gaining great attention in recent years, revolutionizing, and transforming many manufacturing industries, including the food processing sector. The aim of this narrative review is to provide an updated overview of recent developments of Industry 4.0 technologies in digital transformation and process automation of the food processing industry. Our literature review shows the key role of robotics, smart sensors, Artificial Intelligence, the Internet of Things, and Big Data as the main enablers of the Food Processing 4.0. advantages in terms of quality control (sorting during processing with robotics and Artificial Intelligence, for instance), safety (connecting sensors and devices with Internet of Things), and production efficiency (forecasting demand with Big Data). However, detailed studies are still necessary to tackle significant challenges and provide deep insights into each of Food Processing 4.0 enablers such as the development of specific effectors for robotics; miniaturization and portability for sensors; standardization of systems and improve data sharing for Big Data; and reduce initial and maintenance costs of these technologies.